2013
DOI: 10.1242/dev.087601
|View full text |Cite
|
Sign up to set email alerts
|

Coronary veins determine the pattern of sympathetic innervation in the developing heart

Abstract: SUMMARYAnatomical congruence of peripheral nerves and blood vessels is well recognized in a variety of tissues. Their physical proximity and similar branching patterns suggest that the development of these networks might be a coordinated process. Here we show that large diameter coronary veins serve as an intermediate template for distal sympathetic axon extension in the subepicardial layer of the dorsal ventricular wall of the developing mouse heart. Vascular smooth muscle cells (VSMCs) associate with large d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
92
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(102 citation statements)
references
References 34 publications
9
92
0
1
Order By: Relevance
“…Netrin-1 was not expressed in the heart, and cardiac innervation was normal in Ntn1 mutants. Interestingly, a growing body of evidence indicates that innervation of the heart and large arteries is regulated by other molecules, including NGF and the axon guidance molecule Sema3A and its receptor Nrp1 (41)(42)(43). Therefore, sympathetic innervation of cardiovascular targets may be regulated by specific combinations of guidance molecules: Sema3A/Nrp1 for the heart and large arteries and netrin/DCC for resistance arteries.…”
Section: Discussionmentioning
confidence: 99%
“…Netrin-1 was not expressed in the heart, and cardiac innervation was normal in Ntn1 mutants. Interestingly, a growing body of evidence indicates that innervation of the heart and large arteries is regulated by other molecules, including NGF and the axon guidance molecule Sema3A and its receptor Nrp1 (41)(42)(43). Therefore, sympathetic innervation of cardiovascular targets may be regulated by specific combinations of guidance molecules: Sema3A/Nrp1 for the heart and large arteries and netrin/DCC for resistance arteries.…”
Section: Discussionmentioning
confidence: 99%
“…Disturbing epicardial outgrowth results in abnormal development of the coronary vasculature [36]. The hampered response to epinephrine described in the current study could possibly be explained by disruption of the earliest stages of blood vessel formation and NGF production, which is required for normal development of the autonomic nervous system [41].…”
Section: Discussionmentioning
confidence: 63%
“…Finally, recent work showed that normal development of the cardiac veins is required for normal development of the sympathetic nervous system of the heart [41]. This process is driven by nerve growth factor (NGF), secreted by vascular smooth muscle cells in subepicardial blood vessels [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vessels fated to form arteries and capillaries are localized deep within the walls of both the ventricles and the aorta [1][2][3] . However, whilst fluorescent labeling of cells combined with laser-scanning confocal microscopy can provide high resolution images of wholemount-labeled superficial venous/lymphatic vessels 4,5 , the depth of imaging is limited by optical penetration. High-resolution imaging of capillaries and arteries throughout the whole depth of the heart is therefore not possible without some form of tissue clearing.…”
Section: Introductionmentioning
confidence: 99%